Application of the Technological Acceptance Model(TAM) Approach to the Influence of Public Perceptions Using Digital Wallets - Saputra, Elin Panca; Saputro, Achmat Yulyadi; Priyono, Priyono; Kusumo, Aryo Tunjung; Rahman, Taufik (Jurusan Informatika, 2024)
Purpose: This research aims to conduct a study of the perceptions of digital wallet users and how users' reactions influence the benefits of digital wallets in the big city of JakartaDesign/methodology/approach: The research method applied is a quantitative method. The population of this research is digital wallet users in the city of Jakarta. The number of samples applied was 121 respondents according to the purposeful sampling method. The data testing methods applied are convergent validity, discriminant validity, composite reliability and Cronbanch alpha. Data calculations apply Smart PLS 3 software. The results of this study show that trust and perceived risk do not influence user preferences for using digital walletsFindings/result: The results of this research constantly support a number of previous studies related to TAM where perceived usefulness and perceived ease of use play a direct and indirect role in interest in using digital wallets. So the community's perceived usefulness is a variable that has a prominent influence on the preferences of digital wallet users in the city of Jakarta.Originality/value/state of the art: The steps taken from the start of the study to its conclusion were designed to use the TAM approach to determine how the public felt about this particular study. This study uses quantitative research methods and yields two models: an inner model, or structural model, that includes path analysis through Smart PLS 3 data analysis, and an outer model, or measurement model, that includes composite reliability, conbranch alpha, discriminant validity, and convergent validity.